2002
DOI: 10.1021/ja0127279
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyquinol A, a Highly Functionalized Pentaketide Dimer with Antiangiogenic Activity Isolated from Fungal Metabolites

Abstract: A unique pentaketide dimer structure of a novel fungal metabolite with antiangiogenic activity, designated as epoxyquinol A (1), was determined on the basis of NMR spectral data as well as the X-ray crystallographic analysis. 1 inhibits the endothelial migration induced by vascular endothelial growth factor (ED100 = 3 mug/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 14 publications
0
87
1
Order By: Relevance
“…Epoxyquinols A and B (Figure 5a), which are naturally occurring pentaketide dimers, have been isolated from fungal metabolites and found to possess potent antiangiogenic activity. 92,93 It has also been shown that both epoxyquinols A and B block TNF-a-induced NF-kB activation. 87,88 Compared with epoxyquinol A, its structural derivative, epoxyquinone A monomer (Figure 5a), is a potent inhibitor of TNF-a-induced NF-kB activation.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…Epoxyquinols A and B (Figure 5a), which are naturally occurring pentaketide dimers, have been isolated from fungal metabolites and found to possess potent antiangiogenic activity. 92,93 It has also been shown that both epoxyquinols A and B block TNF-a-induced NF-kB activation. 87,88 Compared with epoxyquinol A, its structural derivative, epoxyquinone A monomer (Figure 5a), is a potent inhibitor of TNF-a-induced NF-kB activation.…”
Section: Epoxyquinoidsmentioning
confidence: 99%
“…Interestingly, Kakeya et al (2002) recently identified a natural fungal metabolite, epoxyquinol A, that bears striking structural resemblance to JD. However, epoxyquinol A and JD have opposite enantiomeric compositions.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Kakeya, Osada and co-workers have isolated and determined the structures of epoxyquinols A (1), [2] B (2), [3] and C (3) [4] and epoxytwinol A (4) [5] from an unknown soil fungus, and azaspirene [6] and RK-805 [7] from the fungus Neosartorya sp. (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] That is, diol monomer 18 is oxidized to aldehyde 17, which undergoes 6π-electrocyclization to afford 2H-pyran derivative 16 (Scheme 1). Diels-Alder dimerization of 2H-pyran 16 proceeds to provide epoxyquinols A (1), B (2), and C (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation